Assessment of the fatty acid composition of different parts of zebrafish fed diets incorporated with linseed and sunflower oils (Research, Society and Development, 2021)
This study aimed to evaluate the fatty acid composition of zebrafish fed diets containing linseed oil compared to sunflower oil. First, diets supplemented with linseed and sunflower were formulated, fish were fed for 40 days, and their parts collected for analysis. Diet composition analysis, extraction and derivatization of fatty acids, gas chromatography analysis, RNA extraction and cDNA synthesis, quantitative real-time polymerase chain reaction (qRT-PCR, and statistical analyses were performed. Linseed oil exhibited an omega-3 rich lipid profile. 18:3n-3 content incorporated into the muscle tissue of fish fed linseed oil was 50% higher than that fed sunflower oil. This higher amount of 18:3n-3 favored the production of 20:5n-3 and 22:6n-3 fatty acids by synthetic pathways in the organism since these fatty acids were not initially found in the oil composition. Furthermore, in all analyzed parts of zebrafish that were fed linseed oil, concentration of 20:4n-6 were lower, while 20:5n-3 and 22:6n-3 were higher compared to the same parts fed with sunflower oil. PCR expression assay showed no significant difference, indicating that linseed oil diet was not harmful. Thus, this work evidenced that synthesis of essential fatty acids, primarily omega-3 fatty acids, was greater in zebrafish upon consumption of diets supplemented with linseed oil.